Dental and Periodontal Findings in Hemodialysis Patients - Mudhfar Mohammed Meizel; Nawres Bahaa Mohammed (Medical Journal of Babylon)
Background:End-stage renal disease (ESRD) are more to infections due to their decrease in immune systems and general debilitated health, most of patients with renal failure showing oral symptoms. Objectives:The aim of this study is to assessment the kind and severity of oral symptoms in ESRD patients undergoing hemodialysis and compare these results with healthy, disease-free persons. Materials and Methods:The study involved 40 individuals, comprising 20 hemodialysis patients and 20 healthy control. The patient group was randomly chosen from ESRD patients, while the control group consisted of disease-free persons with normal glomerular filtration rates. The symptoms such as dry mouth, taste changes, halitosis, and mucosal pain, and were oral changes like tongue coating, pallor, ulceration, and enamel hypoplasia. Results:The ESRD patients established significantly more oral changes compared to the control group. These due to metabolic disorders caused by renal failure. Conclusion:there is significant impact of ESRD on the oral health of the patients, with correlation between oral health and ESRD.